Acclimation of marine invertebrate osmolyte systems to low salinity: A systematic review & meta-analysis - Podbielski, Imke; Schmittmann, Lara; Sanders, Trystan; Melzner, Frank (Frontiers in Marine Science, 2022)
Salinity is a major environmental factor shaping the distribution and abundance of marine organisms. Climate change is predicted to alter salinity in many coastal regions due to sea level rise, evaporation, and changes in freshwater input. This exerts significant physiological stress on coastal invertebrates whose body fluid osmolality follows that of seawater (‘osmoconformers’). In this study, we conducted a systematic review and meta-analysis of osmolytes (both organic and inorganic) utilized by osmoconforming marine invertebrates during a >14-day acclimation to reduced salinity. Of the 2,389 studies screened, a total of 56 fulfilled the search criteria. Thirty-eight studies reported tissue osmolyte. Following acclimation to reduced salinity, tissue concentrations of six organic compounds and sodium were consistently reduced across phyla. This suggests that intracellular inorganic ions are not only utilized as a rapid response system during acute exposure to low salinity stress but also, in concert with reductions in organic osmolyte concentrations, during longer-term acclimation. Our systematic review demonstrates that only a few studies (n = 13) have quantified salinity-induced long-term changes in intracellular ion concentrations. In addition, no study has compiled a complete intracellular osmolyte budget. Alanine, betaine, glycine, and taurine are the major organic osmolytes that are universally employed across five phyla. The characterization of organic osmolytes was heavily weighted towards free amino acids (FAAs) and derivatives—neglecting methylamines and methylsulfonium compounds, which can be as important as FAAs in modulating intracellular osmolality. As a consequence, we suggest best-practice guidelines to streamline experimental designs and protocols in osmoregulation research in order to better understand the conserved mechanisms that define the limits of salinity acclimation in marine invertebrates. To our best knowledge, this is the first systematic review and meta-analysis on osmolyte concentrations in osmoconformers acclimated to low salinity. It creates a valuable baseline for future research and reveals large research gaps. Our meta-analysis suggests that there are common osmolyte actors employed across phyla but no uniform concept since osmolyte pool composition and proportions were taxon-specific. In light of future salinity changes and their potential consequences, it becomes more important to understand salinity tolerance capacities and limits.